2022
DOI: 10.1111/rode.12928
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing vulnerability to poverty and assessing the role of universal public works and food security programs to reduce it: Evidence from an eastern Indian state

Abstract: Social protection (SP) programs have become a widespread intervention to strengthen coping strategies in developing countries to improve the well-being of vulnerable households. Past studies have identified the positive impact of SP on ex-post poverty reduction. However, there is relatively scant evidence of the role of SP in reducing vulnerability to poverty (VtP). This study estimates the role of SP, in particular, the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) and public distribution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The finding is in line with past results, showing that there is a negative association between various shocks (death of breadwinners, illness, flood and drought) and transient poverty (Khosla et al, 2023). This suggests that poverty remains high due to the risk household experience and falls into poverty, in line with past empirical findings (Gunther & Harttgen, 2009;Khosla & Jena, 2022;Khosla et al, 2023). However, we find that the non-poor are comparatively less affected by the various shocks.…”
Section: Household Vulnerability To Multidimensional Povertysupporting
confidence: 93%
See 1 more Smart Citation
“…The finding is in line with past results, showing that there is a negative association between various shocks (death of breadwinners, illness, flood and drought) and transient poverty (Khosla et al, 2023). This suggests that poverty remains high due to the risk household experience and falls into poverty, in line with past empirical findings (Gunther & Harttgen, 2009;Khosla & Jena, 2022;Khosla et al, 2023). However, we find that the non-poor are comparatively less affected by the various shocks.…”
Section: Household Vulnerability To Multidimensional Povertysupporting
confidence: 93%
“…In the last two decades, investigating such vulnerability and the livelihood effects of shocks has become an important matter of research and discussion in development economics. In the literature on vulnerability, several methodological studies (Morduch, 2005; Christiaensen & Boisvert, 2000; Skoufias & Quisumbing, 2004; Dercon, 2004; Glewwe and Hall, 1998; Dercon & Krishnan, 2000; Jalan & Ravallion, 1999; Gallardo, 2018) and empirical studies (Günther & Harttgen, 2009; Dercon, 2005; Khosla & Jena, 2022; Khosla et al, 2023) have been conducted using different approaches and country cases. The empirical studies have observed that the share of households at risk of falling into poverty is higher than the currently classified monetary poverty rate.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on poverty vulnerability has proposed several key strategies to reduce poverty vulnerability, for example, traditional finance development (Han et al, 2019; Khandker, 2007; Phan et al, 2023), public fiscal transfer payments (Azeem et al, 2019; Brugh et al, 2018; Li & Huang, 2022; Wang et al, 2021), and social security (Carter & Janzen, 2018; Khosla & Jena, 2022; Tirivayi et al, 2016; Zhang et al, 2020). In addition, informal risk‐coping mechanisms, such as the sale of livestock to smooth consumption, are supported by a large number of documents (Dube & Ozkan, 2022; Fafchamps et al, 1998; Kurosaki, 1995; Ngigi et al, 2021; Rosenzweig & Wolpin, 1993; Udry, 1995).…”
Section: Introductionmentioning
confidence: 99%